PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP OPTIMISME WARGA BINAAN ANAK (KASUS NON NARKOBA) LAPAS ANAK PEKANBARU - Fitri Setiowati; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of guidance in group toward optimism of child inmates. The method in this research used pre experimental method, using One Group Pre-test Post-test Design. This research was done twice before the experiment (pre test) and after experiment (post test) with one group of subject. Analysis data in this research is descriptive analytic used qualitative and quantitative. Subjects in this study were selected by non-probability sampling technique with purposive sampling method consist of 6 child inmates of non-drug cases. This research was conducted by providing guidance in group for 5 times. The result of research shows that there is influence of guidance in group toward optimism of child assisted by 86%, while 14% influenced by other factors coming from theirself and environment.Keywords: Guidance in group, Optimism, Child Inmates